The CGEM-IT readout chain. (26th August 2021) - Amoroso, A.; Baldini Ferroli, R.; Balossino, I.; Bertani, M.; Bettoni, D.; Bianchi, F.; Bortone, A.; Bugalho, R.; Calcaterra, A.; Cerioni, S.; Chiozzi, S.; Cibinetto, G.; et al.
Abstract: An innovative Cylindrical Gas Electron Multiplier (CGEM) detector is under construction for the upgrade of the inner tracker of the BESIII experiment. A novel system has been worked out for the readout of the CGEM detector, including a new ASIC, dubbed TIGER -Torino Integrated GEM Electronics for Readout, designed for the amplification and digitization of the CGEM output signals. The data output by TIGER are collected and processed by a first FPGA-based module, GEM Read Out Card, in charge of configuration and control of the front-end ASICs. A second FPGA-based module, named GEM Data Concentrator, builds the trigger selected event packets containing the data and stores them via the main BESIII data acquisition system. The design of the electronics chain, including the power and signal distribution, will be presented together with its performance.